Clinical impact of controlling nutritional status score on the prognosis of patients with diffuse large B‐cell lymphoma. Issue 3 (3rd July 2020) - Nagata, Akihito; Kanemasa, Yusuke; Sasaki, Yuki; Nakamura, Shohei; Okuya, Toshihiro; Funasaka, Chikako; Kageyama, Akihiko; Shimoyama, Tatsu; Omuro, Yasushi
Abstract: The controlling nutritional status (CONUT) score is a nutritional index calculated from serum albumin and total cholesterol levels and lymphocyte counts. Its role in predicting clinical outcomes of diffuse large B‐cell lymphoma (DLBCL) has not been evaluated. In this retrospective study, data from 476 patients with DLBCL were analyzed. The cutoff value of the CONUT score was set as 4. CONUT score significantly stratified the overall survival (OS) and the progression‐free‐survival (PFS) (5‐year OS, 49.0% vs 83.2%, P < .001; 5‐year PFS, 46.1% vs 73.1%, P < .001) of the patients. Among patients at high‐intermediate or high risk, as per the National Comprehensive Cancer Network International Prognostic Index (NCCN‐IPI), 5‐year OS was lower in patients with high CONUT scores than in those with low CONUT scores (high‐intermediate risk, 51.2% vs 75.5%, P < .001; high risk, 29.9% vs 63.3%, P = .007). Additionally, in patients with high CONUT scores, maintenance of relative dose intensity (RDI) of chemotherapy did not affect the 5‐year OS (RDI > 80% vs RDI ≤ 80%: 59.8% vs 50.9%, P = .73). In the present study, we have demonstrated that the CONUT score is an independent prognostic factor in patients with DLBCL.